Trouble In Gangtok - Satyajit Ray (A Puffin, 2003)
Are you a true professional? Would you like to become one? In The Professional, one of the biggest-selling business books ever to come out of India, Subroto Bagchi showed how one can behave professionally$1 (Bor otherwise$1 (Bin diverse situations, and asked the key question: What does it mean to be a professional? Inspired by that game-changing book, many an aspiring professional has been wanting to test his/her mettle using Bagchi$1 (Bs tools. The Professional Companion fulfils that need. In this do-it-yourself workbook that is meant as a companion volume to The Professional, Bagchi takes you through simple exercises that allow you to understand how professional your approach is in a given context, and helps you develop a wider skill set and a more committed outlook. The Professional Companion is your very own personalized guide to excelling in today$1 (Bs world.s
Keywords: Mystery, Suspense; Mystery -- Mystery; Suspense -- Suspense